Pengaruh Pemberian Mozart Classical Music Terhadap Tingkat Kecemasan Pada Ibu Bersalin Kala I Di Praktek Mandiri Bidan Netti Sumarni Kota Padang. - Ramadhani, Narisha Afifah; Restipa, Ledia; Kesuma, Sari Indah (Alifah Health Science Symposium Proceeding, 2024)
Psychological factors are one of the inhibiting factors in childbirth, thus triggering birth complications. Anxiety is one of them. Based on 2018 West Sumatra RISKESDAS data’s the highest on complications were caused by prolonged labor (5.46%) and hypertension (1.85). The aim of the research was to determine the effect of giving Mozart Classical Music on the level of anxiety in mothers during the first stage of labor at Independent Practice of Midwife Netti Sumarni, Padang City. Research use quantitative with pre-experimental method One Group Pre Test And Post Test approach. Data collection was carried on May 21 - June 28, 2024, sampling technique used Quota Sampling as many 25 mothers in first stage of labor latent phase with direct interviews of ZSAR-S questionnaire, data analyzed univariately and bivariately using Wilcoxone test with  p-value <0.05. The results of study showed the average level of anxiety before given Mozart Classical Music therapy was 57,08 (SD=6.654), after given therapy was 53,96 (SD=6.235) with a difference 3,12. The results also showed there was an effect before and after given Mozart Classical Music therapy p-value 0.000 (p<0.05) on level of anxiety of mothers in first stage of labor latent phase at Independent Practice of Midwife Netti Sumarni, Padang City. The conclusion of this research there is an effect of giving Mozart Classical Music on level of anxiety in mothers in the first stage of labor at Independent Practice of Midwife Netti Sumarni, Padang City. It’s recommended that health workers can facilitate and educate patients in controlling anxiety during the birth period.